The Classical–Basal Spectrum in Pancreatic Ductal Adenocarcinoma: A Developmental Framework for Tumour Cell Plasticity and Clinical Translation - Ikra Khan; Azzadinne Belhaj; Alessandro Gemini; Kenza Azra Ibis; Nouman Darsif; Najoua Rouani; Aude Vanlander; Nouredin Messaoudi (Cancers, 2026)
Transcriptomic profiling reproducibly resolves pancreatic ductal adenocarcinoma (PDAC) into two prognostically divergent tumour-intrinsic programmes—classical/progenitor and basal-like/squamous—accompanied by a separable stromal axis; additional proposed classes are strongly influenced by low tumour cellularity and generalise poorly across datasets. Rather than cataloguing these programmes, this review synthesises evidence that they behave as plastic cell states and proposes an integrative developmental framework for interpreting that plasticity, rather than claiming its discovery. The framework combines a normal-pancreas developmental reference frame, the regulation of state by lineage transcription factors, epigenetic remodelling, oncogenic (KRAS) dosage, stromal instruction, and treatment pressure, and a testable notion of spatial disorganisation. Throughout, we separate robust prognostic evidence—basal-like assignment and low GATA6 expression are consistently associated with worse outcome—from predictive claims: predictive utility remains unproven because no completed prospective trial has assigned treatment according to classical–basal subtype and demonstrated improved clinical outcome from that strategy, and existing signals derive from retrospective or observational analyses. The proposition that the classical–basal spectrum reflects a spatially disordered redeployment of the normal duct’s luminal–basal hierarchy is presented as a hypothesis requiring validation in independent atlases rather than as established biology. We define the falsifiable experiments needed to test the framework and its clinical implications.